2018
DOI: 10.1186/s12871-018-0563-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of anesthesia maintained with sevoflurane or propofol with and without additional monitoring: a prospective, randomized controlled trial

Abstract: BackgroundWe compared cost-effectiveness of anesthesia maintained with sevoflurane or propofol with and without additional monitoring, in the clinical setting of ear-nose-throat surgery.MethodsOne hundred twenty adult patients were randomized to four groups. In groups SEVO and SEVO+ anesthesia was maintained with sevoflurane, in group SEVO+ with additional bispectral index (BIS) and train-of-four (TOF) monitoring. In groups PROP and PROP+ anesthesia was maintained with propofol, in group PROP+ with additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
2
5
0
9
Order By: Relevance
“…The authors noted the necessity of additional monitoring during daily practice. [30] We included the price of an infusion syringe and extension line in the cost analysis of the patients in Group P. A BIS electrode was used in all cases, so this expense was excluded from the cost investigation. In our hospital, it is difficult to estimate the indirect, fixed, and variable costs.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted the necessity of additional monitoring during daily practice. [30] We included the price of an infusion syringe and extension line in the cost analysis of the patients in Group P. A BIS electrode was used in all cases, so this expense was excluded from the cost investigation. In our hospital, it is difficult to estimate the indirect, fixed, and variable costs.…”
Section: Discussionmentioning
confidence: 99%
“…Just as with environmental considerations, the impact goes beyond the costs of the drugs themselves. There is surprisingly little published on comparative costs although one recent study in ENT patients found little to choose between sevoflurane and propofol (no significant difference at 12‐13 euros per hour). What wasn't considered in that study, however, was the cost of other consumables.…”
Section: Do We Need To Consider Costs?mentioning
confidence: 99%
“…A cost-effectiveness és budget-impact analysis keresés 79 találatból összesen 15 publikációt válogattunk be (Baji et al, 2012a, Baji et al, 2012b, Brodszky et al, 2014b, Dasbach et al, 2010, Iversen et al, 2015, Mandel et al, 2014, Marada et al, 2016, Nagy et al, 2014, Scuffham et al, 2006, Vokó et al, 2012, Zemplenyi et al, 2016, Boncz et al, 2010, Brodszky et al, 2010c, Daroczi et al, 2016. Összesen 13 technológiaelemzési jelentés került beválogatásra kézi keresésünk eredményeként (Brodszky et al, 2006a, Brodszky et al, 2006b, 2010b, 2010, 2010a, 2011a, 2011, Brodszky et al, 2011b, Brodszky et al, 2011c, Brodszky et al, 2013 a magyar nyelvű magyarországi irodalom helyi keresése alapján további hét közleményt válogattunk be (Bodnár et al, 2010, Borsos et al, 2006, Brodszky et al, 2010e, Harangozó et al, 2008, József, 2006, Kósa József et al, 2008. A keresés frissítése 314 találatot eredményezett, amelyből 14 publikáció került beválogatásra (Brodszky et al, 2020, Fejes et al, 2019, Vallejo-Torres et al, 2018, Trapero-Bertran et al, 2018, Németh et al, 2018, Coyle et al, 2018, Bocskai et al, 2018…”
Section: A Beválogatott Publikációk Jellemzőiunclassified
“…Összesen 13 technológiaelemzési jelentés került beválogatásra kézi keresésünk eredményeként (Brodszky et al, 2006a, Brodszky et al, 2006b, 2010b, 2010, 2010a, 2011a, 2011, Brodszky et al, 2011b, Brodszky et al, 2011c, Brodszky et al, 2013 a magyar nyelvű magyarországi irodalom helyi keresése alapján további hét közleményt válogattunk be (Bodnár et al, 2010, Borsos et al, 2006, Brodszky et al, 2010e, Harangozó et al, 2008, József, 2006, Kósa József et al, 2008. A keresés frissítése 314 találatot eredményezett, amelyből 14 publikáció került beválogatásra (Brodszky et al, 2020, Fejes et al, 2019, Vallejo-Torres et al, 2018, Trapero-Bertran et al, 2018, Németh et al, 2018, Coyle et al, 2018, Bocskai et al, 2018, Baji et al, 2018, Rencz et al, 2017, Péntek et al, 2017b, Péntek et al, 2017c, Meszner et al, 2017, Kobelt et al, 2017.…”
Section: A Beválogatott Publikációk Jellemzőiunclassified
See 1 more Smart Citation